PENGEMBANGAN STRATEGI UNTUK MENINGKATKAN KINERJA GURU MENGGUNAKAN ANALISIS SITOREM - Rika Widiastuti; Soewarto Hardhienata; Rais Hidayat; Graciano Lucky Scovier (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Teacher performance is a crucial factor in improving educational quality, particularly in private vocational schools managed by foundations. Although many studies have identified factors influencing teacher performance, few provide practical and prioritized strategies for improvement. This study aims to develop an optimal strategy for improving teacher performance using Scientific Identification Theory to Conduct Operation Research in Education Management (SITOREM) analysis. A quantitative survey was conducted involving 156 foundation-employed teachers from private vocational schools in Pontianak City, Indonesia. The study examined organizational climate, teacher empowerment, work motivation, ICT effectiveness, and teacher performance. SITOREM analysis was applied to identify priority indicators that require immediate improvement and indicators that should be maintained. The results show that several indicators related to leadership support, teacher participation in decision-making, motivational reinforcement, and ICT utilization are strategic priorities for improvement. This study offers practical contributions for school management by translating empirical findings into actionable and prioritized improvement strategies.